Cognitive impairment in CKD patients: a guidance document by the CONNECT network - Bolignano, Davide; Simeoni, Mariadelina; Hafez, Gaye; Pepin, Marion; Gallo, Antonio; Altieri, Manuela; Liabeuf, Sophie; Giannakou, Konstantinos; De, Ananya; Capasso, Giovambattista; CONNECT Action (Cognitive Decline in Nephro-Neurology European Cooperative Target) collaborators; Spasovski, Goce (Oxford University Press (OUP), 2024)
Cognitive impairment is a prevalent and debilitating complication in patients with chronic kidney disease (CKD). This position paper, developed by the Cognitive Decline in Nephro-Neurology: European Cooperative Target network, provides guidance on the epidemiology, risk factors, pathophysiology, diagnosis and clinical management of CKD-related cognitive impairment. Cognitive impairment is significantly more common in CKD patients compared with the general population, particularly those undergoing haemodialysis. The development of cognitive impairment is influenced by a complex interplay of factors, including uraemic neurotoxins, electrolytes and acid-base disorders, anaemia, vascular damage, metabolic disturbances and comorbidities like diabetes and hypertension. Effective screening and diagnostic strategies are essential for early identification of cognitive impairment utilizing cognitive assessment tools, neuroimaging and circulating biomarkers. The impact of various drug classes, including antiplatelet therapy, oral anticoagulants, lipid-lowering treatments and antihypertensive drugs, on cognitive function is evaluated. Management strategies encompass pharmacological and non-pharmacological interventions, with recommendations for optimizing cognitive function while managing CKD-related complications. This guidance highlights the importance of addressing cognitive impairment in CKD patients through early detection, careful medication management and tailored therapeutic strategies to improve patient outcomes.
Keywords: CKD; cognitive impairment; neuroimaging; quality of life; uraemic neurotoxins